THE LINGUISTIC LANDSCAPE OF THE UNIVERSE AND THE QUESTION OF ITS ESSENCE - Kuchimova Parizod Tulqin qizi (Modern American Journals, 2025)
This article is about linguistic landscape of the world is a multifaceted, evolving system that reflects the interaction between languages and language communities at a global level. Its structure is determined by the geographical distribution of languages and language families, their genetic and typological characteristics, as well as the historical connections and frequency of language interaction.
Keywords: Linguistic, linguistic landscape, language, communicative domain, aspect, global language landscape, functional elements.